Glutamatergic neurons in the medial prefrontal cortex mediate the formation and retrieval of cocaine‐associated memories in mice. (7th February 2019) - Zhang, Tong; Yanagida, Junko; Kamii, Hironori; Wada, Shintaro; Domoto, Masaki; Sasase, Hitoki; Deyama, Satoshi; Takarada, Takeshi; Hinoi, Eiichi; Sakimura, Kenji; Yamanaka, Akihiro; Maejima, Takashi; et al.
Abstract: In drug addiction, environmental stimuli previously associated with cocaine use readily elicit cocaine‐associated memories, which persist long after abstinence and trigger cocaine craving and consumption. Although previous studies suggest that the medial prefrontal cortex (mPFC) is involved in the expression of cocaine‐addictive behaviors, it remains unclear whether excitatory and inhibitory neurons in the mPFC are causally related to the formation and retrieval of cocaine‐associated memories. To address this issue, we used the designer receptors exclusively activated by designer drugs (DREADD) technology combined with a cocaine‐induced conditioned place preference (CPP) paradigm. We suppressed mPFC neuronal activity in a cell‐type– and timing‐dependent manner. C57BL/6J wild‐type mice received bilateral intra‐mPFC infusion of an adeno‐associated virus (AAV) expressing inhibitory DREADD (hM4Di) under the control of CaMKII promotor to selectively suppress mPFC pyramidal neurons. GAD67‐Cre mice received bilateral intra‐mPFC infusion of a Cre ‐dependent AAV expressing hM4Di to specifically silence GABAergic neurons. Chemogenetic suppression of mPFC pyramidal neurons significantly attenuated both the acquisition and expression of cocaine CPP, while suppression of mPFC GABAergic neurons affected neither the acquisition nor expression of cocaine CPP. Moreover, chemogenetic inhibition of mPFC glutamatergic neurons did not affect the acquisition and expression of lithium chloride‐induced conditioned place aversion. These results suggest that the activation of glutamatergic, but not GABAergic, neurons in the mPFC mediates both the formation and retrieval of cocaine‐associated memories. Abstract : To investigate whether neurochemically discrete neuronal populations in the medial prefrontal cortex (mPFC) are causally related to the formation and retrieval of cocaine‐associated memories, we used the DREADD technology combined with a cocaine‐induced conditioned place preference (CPP) paradigm. Chemogenetic suppression of mPFC pyramidal neurons significantly attenuated both the acquisition and expression of cocaine CPP, while suppression of mPFC GABAergic neurons affected neither the acquisition nor expression of cocaine CPP. Our results suggest that the activation of glutamatergic, but not GABAergic, neurons in the mPFC mediates both the formation and retrieval of cocaine‐associated memories.